Philosophical Study of Universal Rights (HAAS) and Human Rights (HAM): Exegesis of Al-'Ālamīn's Concept in the Al-Qur'ān - Ismail, M. Syukri; Khaer, Abu (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2024)
This paper is intended to explore the holistic philosophy of al-ʿālamīn in al-Qur’an as the basis for Universal Rights, Hak Asasi Alam Semesta (HAAS), for the lack of comprehensiveness of Human Rights, Hak Asasi Manusia (HAM), which tends to be anthropocentric-materialistic-secularistic. This research is qualitative research relying on the literature review method. The analytical tool used in this research is the Hermeneutical-philosophical paradigm of human rights and international law contained in the al-ʿālamīn concept. Al-ʿālamīn, God Sustainer of Humans, has been, is, will always be translated and interpreted with the embodiment in the form of Human Rights. Not only human rights, it also needs to be conceptualized and implemented in the discourse of Universal Rights where God is the Custodian of the Universe. HAM does not necessitate human religiosity. It is just the fulfillment of human rights to one creature, named human. HAAS, in addition to fulfilling human rights religiously and spiritually, is also primarily a blessing for the universe, including the fulfillment of human rights for all forms of natural resources, such as plants, animals, jinn, earth, planets, galaxies and so on. Therefore, the five main things that make up maqashid al-shari'ah, namely protecting religion, soul, lineage, property and mind, which have an anthropocentric tendency, become more holistic when fulfilled by protecting the universe, hifz al-ʿālamīn. Tulisan ini dimaksudkan untuk mengeksplorasi filosofi holistik al-ʿālamīn dalam al-Qur'an sebagai dasar Hak Asasi Universal, Hak Asasi Alam Semesta (HAAS) karena kurang komprehensifnya Hak Asasi Manusia (HAM) yang cenderung antroposentris-materialistik-sekularistik. Penelitian ini merupakan penelitian kualitatif yang mengandalkan metode kajian pustaka. Alat analisis yang digunakan dalam penelitian ini adalah paradigma hermeneutika-filosofis hak asasi manusia dan hukum internasional yang terkandung dalam konsep al-'ālamīn. Al-'Ālamīn, Tuhan Pemelihara Manusia, telah, sedang, dan akan selalu diterjemahkan dan ditafsirkan, dengan pengejawantahannya dalam bentuk HAM. Tidak hanya HAM, HAM juga perlu dikonseptualisasikan dan diimplementasikan dalam wacana HAAS, Tuhan Pemelihara Alam Semesta. HAM tidak mengharuskan adanya religiusitas manusia. HAM hanyalah pemenuhan hak asasi manusia terhadap satu makhluk, yaitu manusia. HAI, selain memenuhi hak asasi manusia secara religius dan spiritual, juga utamanya adalah menjadi rahmat bagi alam semesta, termasuk pemenuhan hak asasi manusia terhadap segala bentuk sumber daya alam, seperti tumbuhan, hewan, jin, bumi, planet-planet, galaksi, dan lain sebagainya. Oleh karena itu, lima hal utama yang membentuk maqashid al-syari'ah, yaitu menjaga agama, jiwa, nasab, harta, dan akal, yang memiliki kecenderungan antroposentris, menjadi lebih holistik ketika dipenuhi dengan menjaga alam semesta, hifz al-ʿālamīn.